Qualidade de vida de mães de crianças com história de hospitalização em unidade de terapia intensiva neonatal - Oliveira, Sheila Jaqueline Gomes dos Santos (2022)
Introduction: There is evidence that the Neonatal Intensive Care Unit (NICU) environment can have a negative impact on maternal psychological well-being, especially in low- and middle-income settings. However, most studies on stress and quality of life in mothers of newborns requiring intensive medical care have measured patient-centered outcomes at only one point in time. Objective: To evaluate outcomes focused on mothers of children with a history of hospitalization in the NICU of a usual risk maternity hospital in the state of Sergipe. Method: We carried out a longitudinal study with serial evaluation in a region with the worst socioeconomic indicators in Brazil. Mothers who had newborns hospitalized in the NICU were included. primary outcome was quality of life, measured by the WHOQOL-BREF instrument of the World Health Organization. Secondary outcomes included levels of anxiety (Spielberger State-Trait Anxiety Inventory) and depressive symptoms (Beck Depression Inventory). Results: Fifty-four mothers were included. During the first 48 hours after admission to the NICU, the median quality of life score was 62.5 (IQR 56.3-68.8), and severe levels of state anxiety were observed in 61.1% of the patients. mothers. A positive relationship was observed between levels of state anxiety (p = 0.003), depressive symptoms (p < 0.001) and length of stay in the NICU. After 6 months of birth, lower quality of life scores were observed among mothers of newborns with neonatal asphyxia and congenital malformations. A significant improvement in the mothers' global quality of life score was observed only 12 months after the child's birth, which remained unchanged at the 24-month assessment. Conclusion: The present study found significant changes in maternal mental health and quality of life scores at the time of admission of newborns to the NICU. Despite the improvement in these outcomes at discharge, we observed an influence of length of hospital stay, levels of anxiety and depressive symptoms in this population. In addition, changes in quality of life may be associated with children's clinical conditions over time.